Pencegahan Tindak Pidana Perjudian Online - Muhammad Yanuar Vernanda Saputra; Edi Pranoto (Amal Insani Foundation, 2023)
The crime of online gambling is an act that is prohibited and is a form of action that is contrary to religious, moral and positive legal norms. The problem of gambling has existed for a long time, gambling activities are considered to be something that is usually done by the community, therefore gambling is difficult to eradicate. The emergence of the internet made gambling even more varied, gamblers did not need to meet other players to play gambling. The problems are formulated as follows: (1) How the Police Prevent Online Gambling Crimes in the Legal Area of the Grobogan Police. (2) What Obstacles and Obstacles Did the Police Encounter in Eradicating Online Gambling Crimes in the Legal Area of the Grobogan Police? The research objectives to be achieved are to find out and analyze the police's methods of preventing online gambling crimes, as well as to find out the police's constraints and obstacles in handling online gambling crimes in the jurisdiction of the Grobogan District Police. in the jurisdiction of the Grobogan Police. The legal basis for online gambling is article 27 paragraph 2 in conjunction with Article 45 paragraph 1 of Law No. 19 of 2016 concerning Information and Electronic Transactions